THE EFFECTS OF WORK DISCIPLINE, WORK LOYALTY, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE REGIONAL TAX DIVISION I AT THE REGIONAL REVENUE AGENCY OFFICE OF BATAM CITY - Saputra, Tengku Izan; Sabri, Sabri; Sumardin, Sumardin (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of work discipline, work loyalty, and work motivation on the performance of Regional Tax I employees at the Batam City Regional Revenue Agency Office. The study used a quantitative, census-based approach, with the entire population of 81 employees serving as respondents. Data were collected through a questionnaire that had been tested for validity and reliability. The test results showed that all statement items were valid (r > 0.218, p < 0.05) and reliable (Cronbach's Alpha > 0.60). Data analysis was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that partial work discipline has a positive and significant effect on employee performance; work loyalty also has a positive and significant effect, and work motivation has a positive and significant effect, with the latter being the most dominant contributor. Simultaneously, work discipline, work loyalty, and work motivation have a significant effect on employee performance. The coefficient of determination of 0.719 indicates that 71.9% of the variation in employee performance is explained by the three independent variables, with the remaining 28.1% attributed to other factors outside the study. This finding emphasizes the importance of integrated human resource management in improving the performance of public sector employees.